2020
DOI: 10.1038/s41598-020-69413-0
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of IL-4 and IL-6 on rat neonatal target cardiac cells

Abstract: The nature of the early post-natal immune response in rodents appears to influence cardiac regeneration even though the underlying molecules remain poorly understood. Consistent with this idea, we show now significant changes in the expression of immune and cell movement gene pathways in heart samples from 1-and 7-day-old rats with ventricle resection. We then tested whether conditioned media from adult M2 anti-inflammatory macrophages target neonatal cardiac cells to a pro-regenerative like phenotype compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 50 publications
1
16
0
1
Order By: Relevance
“… 35 , 36 Our findings provide direct evidence of UTI protecting tight junction proteins in pulmonary capillary endothelial cells by regulating the function of macrophages. It is reported that a conditioned medium of M2 type macrophages can upregulate neonatal cardiomyocyte proliferation 37 and a conditioned medium of peritoneal macrophage from CO-treated rats stimulated endothelial cell proliferation. 38 Such evidence supports the view that macrophages can interfere with endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“… 35 , 36 Our findings provide direct evidence of UTI protecting tight junction proteins in pulmonary capillary endothelial cells by regulating the function of macrophages. It is reported that a conditioned medium of M2 type macrophages can upregulate neonatal cardiomyocyte proliferation 37 and a conditioned medium of peritoneal macrophage from CO-treated rats stimulated endothelial cell proliferation. 38 Such evidence supports the view that macrophages can interfere with endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…IL-4 signals via IL-4Rα/IL-13Rα1, a hybrid receptor used by both IL-4 and IL-13. It is noteworthy that the expression of this hybrid receptor is impaired in HF patients [69,70]. Although IL-4 does not suppress cardiac fibrosis, it enhances cardiac function by improving cardiac metabolic functions possibly through signaling via this hybrid receptor to promote M2 macrophage polarization and suppression of cardiac inflammatory response [67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the expression of this hybrid receptor is impaired in HF patients [69,70]. Although IL-4 does not suppress cardiac fibrosis, it enhances cardiac function by improving cardiac metabolic functions possibly through signaling via this hybrid receptor to promote M2 macrophage polarization and suppression of cardiac inflammatory response [67][68][69][70]. Therefore, it is plausible that upregulation in IL-4 signaling in the sac/val treated ZO rats might have contributed to further improvements in DD compared to val alone.…”
Section: Discussionmentioning
confidence: 99%
“…Further, these studies did not identify a functional role of IL-6 generation. IL-6 is a pleiotropic cytokine that has many functions in the heart including regulation of cardiomyocyte hypertrophy and apoptosis and polarization of immune responses [ 57 , 73 , 74 , 75 ]. Additionally, there is abundant evidence for IL-6 influencing fibroblast functions including proliferation [ 76 ] and myofibroblast conversion [ 23 , 76 ].…”
Section: Discussionmentioning
confidence: 99%